Policy Recommendations for Reducing Educational Disparities: A Chaos Theory Perspective - Pearnpitak, Kittipong (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2024)
This article presents the application of chaos theory in educational systems to reveal the complexities and uncertainties inherent in these systems. Chaos theory offers a new perspective on understanding and reducing educational disparities by analyzing personalized learning adaptation and fostering collaborative networks. The article proposes policy recommendations focused on transforming learning approaches, particularly in removing systemic obstacles, tailoring education to meet students' needs, engaging communities, integrating technology, and implementing continuous assessment. These strategies aim to achieve educational equity for all. Moreover, the study underscores the necessity for profound systemic change and the incorporation of contemporary theories to craft effective solutions. This approach advocates for a resilient and adaptable educational environment that meets the evolving needs of future learners.